Application of Hybrid N-S/DSMC Method in Hypersonic Transitional Flow - Li, Zhonghua; Li, Zhihui; Dang, Leining; Bai, Zhiyong (Journal of Environmental Accounting and Management, 2026)
A hybrid N-S/DSMC method is presented and applied to solve the three-dimensional hypersonic transitional flows by employing the MPC (modular Particle-Continuum) technique based on the N-S and the DSMC method. A sub-relax technique is adopted to deal with information transferring between the N-S and the DSMC. The hypersonic flows around a plate and a blunt cone under different Kn numbers are simulated by using the hybrid N-S/DSMC method. The present computations are found in good agreement with other experimental results. The present method provides an efficient way to predict the hypersonic aerodynamics in near-continuum transitional flow regime.